Experiments on helicons in DIII-D—investigation of the physics of a reactor-relevant non-inductive current drive technology*Paper based on contribution EX/P3-22 presented at IAEA FEC, Kyoto, October 2016. (27th July 2018) - Pinsker, R.I.; Prater, R.; Moeller, C.P.; deGrassie, J.S.; Petty, C.C.; Porkolab, M.; Anderson, J.P.; Garofalo, A.M.; Lau, C.; Nagy, A.; Pace, D.C.; Torreblanca, H.; et al.
Abstract: Experiments have begun in DIII-D to evaluate a toroidally-directed spectrum of helicon waves (also known as 'very high harmonic fast waves', 'fast waves in the lower hybrid range of frequencies', or 'whistlers') that can generate efficient non-inductive current drive by Landau absorption in a reactor plasma. Modeling has shown (Prater et al 2014 Nucl. Fusion 54 083024) that non-inductive current drive at mid-radius ( ρ 0.5) should be achievable in DIII-D with fast waves at 0.5 GHz in high-beta conditions with an efficiency twice that of other non-inductive current drive tools currently available on DIII-D (neutral beams and electron cyclotron current drive). An innovative traveling wave antenna (TWA) of the 'comb-line' type with 12 radiating modules has been constructed, installed in DIII-D, and has been tested at very low power (<0.4 kW) to evaluate the antenna coupling in the linear regime, and to test technological aspects of such structures in the tokamak environment. Results show favorably strong antenna/plasma coupling in several plasma regimes, most significantly in the high-beta ELMing H-mode case with calculated full first-pass absorption of the helicon waves in the desired mid-radius region. No evidence of significant excitation of the undesirable slow wave was found when the total magnetic field adjacent to the structure was approximately aligned with the tilted Faraday screen of the antenna. The implications of these results for a high-power experiment currently under construction are discussed.